2007
DOI: 10.1186/1471-2261-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in P wave morphology in healthy subjects

Abstract: BackgroundWe have previously documented significant differences in orthogonal P wave morphology between patients with and without paroxysmal atrial fibrillation (PAF). However, there exists little data concerning normal P wave morphology. This study was aimed at exploring orthogonal P wave morphology and its variations in healthy subjects.Methods120 healthy volunteers were included, evenly distributed in decades from 20–80 years of age; 60 men (age 50+/-17) and 60 women (50+/-16). Six-minute long 12-lead ECG r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 35 publications
9
59
1
Order By: Relevance
“…Forty ethnically-, age-and gender-matched, healthy subjects were selected for a 1:1 case-control comparison from a database of healthy volunteers recruited in Southern Sweden. 12 The study was approved by the local ethics committees and complied with the Declaration of Helsinki. All subjects gave informed consent to participation.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty ethnically-, age-and gender-matched, healthy subjects were selected for a 1:1 case-control comparison from a database of healthy volunteers recruited in Southern Sweden. 12 The study was approved by the local ethics committees and complied with the Declaration of Helsinki. All subjects gave informed consent to participation.…”
Section: Patient Populationmentioning
confidence: 99%
“…either positive or biphasic in orthogonal lead Z and positive in leads X and Y, are the most common morphological types that are equally common in healthy population. While Type 1 is more common in adolescents and young adults, 12,22 Type 2 is the predominant morphology in elderly, 12 and commonly observed in patients with paroxysmal atrial fibrillation. 16,23 Type 3 (biphasic P wave in inferior leads) corresponding to the advanced interatrial block with retrograde left atrial activation has not been observed in our cohort of healthy controls, but was present in one ARVC patient who did not have any structural right ventricular abnormality by echo or MRI.…”
Section: P Wave Morphologymentioning
confidence: 99%
“…25,26 Unfiltered, signal-averaged P waves were analyzed to determine P wave morphology. 19,20,24,25 Following high-pass (0.5 Hz) and bandstop (50 Hz) filtering the QRS complexes were 4 automatically identified and grouped according to similarity (a cross-correlation coefficient, ρ > 0.9). P waves were extracted using 250 ms wide signal windows preceding each QRS complex.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…The method used is described in detail elsewhere. 19,20,25 The morphology was subsequently classified into one of three predefined classes ( …”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation